Should National Development Banks be Subject to Basel III? - Gottschalk, Ricardo; Castro, Lavinia B.; Xu, Jiajun (Review of political economy, 2022)
We address the question: What are the potential impacts of Basel III capital framework for National Development Banks (NDBs) upon their ability to fulfil their developmental mandate? We compare three large NDBs' experiences with Basel III implementation: Brazilian Development Bank, China Development Bank and Germany's KfW. We find that the biggest constraint from Basel III comes less from its levels of comprehensiveness and complexity and more from tightening the levels of capital requirements and demanding better capital quality. The disincentive to the use of internal models and changes in the method for the calculation of operational risks may result in a substantial increase in required capital. Meanwhile, the new large exposure rule may dilute the banks' focus on large, infrastructure projects; the high-risk weights for exposures to project finance and equity may hinder NDBs from using these financing modalities extensively to support large and complex projects and activities that involve innovation financing.